Penanaman Modal Dan Pertumbuhan Ekonomi Tingkat Provinsi Di Indonesia - Rahma Dian Hapsari; Imam Prakoso (Jurnal Ekonomi dan Bisnis, 2016)
This research examines the impact whether foreign direct investment (PMA) can significantly influence the gross domestic regional product ( PDRB ) and how moderation variable of Unemployment Rate (TPT) and Human Development Index (IPM) also influence to Indonesian provinces as the research objects of this study. The data was taken from 2004-2013 (10 years). By using General Methods of Moments (GMM), this research shows PMA does not have any impact on economic growth. On the other hand, domestic direct investment (PMDN) is able to increase economic growth. This implies that PMA only funded the needs to less strategic investment sector. To boost up evenly the provincial economic growth, government should increase the incentive on investment to attract foreign investors to invest on less strategic sectors, and create incentive for domestic investors to maintain the business. Another conclusion is Indonesian workers are not developed due to the presence of PMA, and it indicates that there is no transfer of technology. Government needs to maintain PMDN and attract investors to invest in other sectors that are still not efficiently managed by PMDN.